A visual analysis of immunobiological coverage, its infrastructure, and effects in the state of Bahia - Nascimento, Gabriel de Almeida; dos Reis, Francisco Rodrigo Moreni; Novais, Renato Lima; de Sousa, Daniel Xavier; Almeida, Antonio Gabriel Souza (Seven Editora, 2023)
The article illustrates the performance of the National Immunization Program (PNI) in Bahia, the vaccination coverage of the number of inhabitants, as well as the correlation with investment in health, through the extraction and analysis of data from DATASUS, IBGE, and FNS. It appears that although the investment in health in the analyzed period has been relevant, the logistics and storage of vaccines are still very precarious, given the lack of infrastructure, such as storage chambers for vaccines needed in the municipalities of Bahia. Some pathologies such as whooping cough, poliomyelitis, and hepatitis, in the face of vaccination coverage, are treated individually and graphically illustrated, to demonstrate weaknesses in the performance of the PNI and how the population’s adherence to movements contrary to Brazilian vaccination campaigns, influence and bring serious systemic concerns to the medical and scientific community. The visual analysis of this article graphically demonstrates some of the known outbreaks of diseases, as well as the history of vaccine coverage of immunobiological, and intends to elucidate a method that can help in future decision-making. DOI: https://doi.org/10.56238/colleinternhealthscienv1-133